A COMPARATIVE STUDY OF SERVICE QUALITY BEFORE AND AFTER THE IMPLEMENTATION OF JKN ON PRIVATE AND PUBLIC HOSPITALS - Cecilia, Angelin .; Saerang, David P.E; Tasik, Hizkia . (Universitas Sam Ratulangi, 2018)
Abstract: The right to have an adequate level of life, health, and welfare of people is a part of human right and recognized by all nations in the world, including Indonesia. The problem is that not all citizens of Indonesia can afford health care services. On December 31, 2013 the government established BPJS as the administrator of the National Health insurance of Indonesia called JKN (Jaminan Kesehatan Nasional). JKN helps the citizens, but as for the Hospitals, there are so many changes that exhibit and they need to change their payment system from fee for service to INACBGâ€™s. With INACBG the Hospitals will Receive the payment after they make monthly claim. Currently, BPJS is experiencing deficit, and this is effecting the claim process.Â The purpose of this study is to make a comparison of service quality of the hospitals before and after the implementation of JKN. Using Wilcoxon signed rank test and descriptive analysis. It is found that there is no significant difference of the service quality of Hospitals before and after the implementation of JKN and the users want to use JKN again for financial ease. In order to make JKN a successfull program, the government need to make sure that all of the parties within the cycle of JKN need to work together.Â Keyword: bpjs, jkn, health care, service quality.